Kawasaki disease with peripheral gangrene and autoamputation - an extremely rare complication: a case report - Chaitanya Varma; Shrikiran Aroor; Suneel C Mundkur; Karthick Annamalai (Our Dermatology Online, 2012)
Kawasaki disease (KD) is a form of acute vasculitis involving small and medium sized arteries. Ischemic necrosis of the extremities is a very rare and potentially severe complication of KD. Here we present a case of KD with peripheral gangrene and auto amputation, which is the first such case to be reported from India and the fourteenth case in medical literature. A one year old child with KD and peripheral gangrene was started on aspirin. The digital gangrene resolved on follow up with amputation of the tip of the right index finger.